Study on deformation, damage, and energy dissipation characteristics of limestone under impact loading - Bo Tian; PengFei Gao (AIP Advances)
This study investigates wet–dry cycled limestone specimens through dynamic impact loading experiments using a split Hopkinson pressure bar system. The strain field evolution mechanisms were systematically characterized via the digital image correlation technique. Critical analyses were performed on energy dissipation behavior and fractal dimension evolution during impact compression processes, with particular emphasis on their dependence on loading intensities and wet–dry cycling frequencies. The experimental findings offer critical empirical references for engineering design and construction practices in geotechnical applications.